Novel flavonoids as anti-cancer agents: mechanisms of action and promise for their potential application in breast cancer. (11th August 2014) - Martinez-Perez, Carlos; Ward, Carol; Cook, Graeme; Mullen, Peter; McPhail, Donald; Harrison, David J.; Langdon, Simon P.
Abstract : Flavonoids are a large group of ubiquitous polyphenolic secondary metabolites in plants with a wide range of properties, including a widely reported anti-cancer effect. The present review focuses on the different known mechanisms partaking in said anti-tumour effects, with particular emphasis on breast cancer. Their structure and reactivity allows flavonoids to work as antioxidant agents and phyto-oestrogens, modulating oestrogen signalling and metabolism to induce an overall anti-proliferative response. Other effects include the ability of flavonoids to modulate the CYP1 (cytochrome P450 1) and ABC (ATP-binding cassette) protein families, involved in carcinogenesis and drug delivery respectively. They can also induce apoptosis and cell cycle arrest and regulate other signalling pathways involved in the development and progression of cancer. In conclusion, there is accumulating evidence on the versatility of flavonoids and the numerous activities contributing to their anti-tumour effect. The complex, yet effective, mechanism of action of flavonoids, together with their interesting pharmacological properties, is the basis for their potential application in breast and other cancers. This rationale has led to the current interest in the application of flavonoids, including clinical trials currently underway and the development of novel flavonoids with improved properties, which hold great promise for tackling breast cancer.